FIGURATIVE LANGUAGE IN TAYLOR SWIFT’S SONGS (A SEMANTIC ANALYSIS) - Suleman Bouti; Rusni Podungge; Irmawaty Umar; Meity Dasinsingon (Jurnal Bahasa, Sastra, dan Budaya, 2023)
This study aimed to find out the types of figurative language meaning in Taylor Swift’s songs. There are two songs by Taylor Swift in the album 1989 with the title blank space and new romantics were used in this research as the data. This research has conducted with used descriptive qualitative method. The approach used in this research is a semantic analysis based on linguistics theory. This research used two main theories by Abram (1999), which focuses on analyzing the types of figurative language and the theory of meaning by Leech (1974) which focuses on analyzing the meaning in blank space and new romantic songs. The technique of collecting the data used library research. The data were analyzed by identifying, classifying, and analyzing. This research indicated seven types of figurative language were found in this research. As the result, there are 6 types of metaphor, 6 types of simile, 2 types of personification, 4 types of hyperbole, 12 types of symbolism,  1 type of irony, and 2 types of paradox. Furthermore, the researcher also found 5 types of semantic meaning in blank space and new romantic songs. There are 5 types of connotative meaning, 11 types of affective meaning, 9 types of social meaning, 1 type of conceptual meaning, and 2 types of collocative meaning.